Alloy negative electrode material, preparation method thereof and fluorine ion thermal battery prepared from alloy negative electrode material

By using alloyed rare earth metals and highly reactive metal negative electrode materials in fluoride ion thermal batteries, the problem of hindered fluorination reaction during high-temperature discharge is solved, and a higher discharge depth and energy density are achieved.

CN119560547APending Publication Date: 2025-03-04CHINA ELECTRONIC TECH GRP CORP NO 18 RES INST
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411652924.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-19
Publication Date
2025-03-04

AI Technical Summary

Technical Problem

When fluoride ion thermal batteries are discharged at high temperatures, due to the hindering of fluoride from the highly reactive metal negative electrode product, the fluorination reaction is limited to the grain surface, which seriously affects the discharge capacity and energy density.

Method used

The alloy negative electrode material is used, including 0.5% to 30% rare earth metal and 70% to 99.5% high-reactive metal, and is prepared by high-temperature smelting and treated by plasma rotary electrode method to generate alloy powder to improve the ionic conductivity of the negative electrode material.

Benefits of technology

Through the reasonably designed alloyed negative electrode, a fast fluorine ion transmission network is built, which reduces the internal discharge resistance, increases the discharge depth and energy density, and extends the discharge time.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119560547A_ABST
    Figure CN119560547A_ABST
Patent Text Reader

Abstract

The invention discloses an alloy negative electrode material, a preparation method thereof and a prepared fluorine ion thermal battery, rare earth metal and high-activity metal are alloyed through a metallurgical technology to obtain the uniform and stable alloy negative electrode material, and the alloy negative electrode material is applied to the fluorine ion thermal battery. In the obtained alloy material, through the synergistic effect of rare earth metal and active metal components, a fluorine ion rapid transmission network is constructed in situ in a metal negative electrode, the negative electrode ionic conductivity is improved, a passivation layer formed on a negative electrode electrolyte interface after single active metal is discharged is overcome, and the utilization rate of the metal negative electrode material is effectively improved; and the discharge performance of the fluorine ion thermal battery is further improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of fluoride ion thermal batteries, and in particular relates to an alloy negative electrode material and a preparation method thereof, and a prepared fluoride ion thermal battery. Background Art

[0002] A thermal battery is a type of irreversible battery that uses a molten eutectic salt as an electrolyte. Due to the insulating properties of the eutectic salt at room temperature and the high ionic conductivity in the molten state, thermal batteries have the characteristics of fast response speed, strong instantaneous high-power output capability, resistance to harsh environments, long storage life, and high reliability. They are widely used in military fields such as aerospace, missiles, and torpedoes. At present, conventional thermal batteries are mainly lithium-based thermal batteries with lithium ions as the carrier. With the transmission of electrons in the external circuit, lithium ions migrate from the negative electrode to the positive electrode to complete the entire discharge process of the lithium-based thermal battery. However, the melting point of lithium metal and the thermal decomposition temperature of the sulfide positive electrode are low, which can easily cause short circuits and thermal runaway during the discharge process of the thermal battery, making the safety and reliability of lithium-based thermal batteries when working at high temperatures one of the difficult problems to solve.

[0003] Fluoride ion thermal battery is a primary battery with anionic fluoride ions as charge carriers. During the discharge process, fluoride ions migrate from the positive electrode to the negative electrode. Highly active metal negative electrode materials and fluoride positive electrode materials usually have high melting points and thermal decomposition temperatures. In addition, metals such as Mg and Al have small atomic weights as negative electrodes and can react with multiple fluoride ions, and have high theoretical specific energy. Therefore, compared with lithium-based thermal batteries, fluoride ion thermal batteries have higher energy density and good safety and reliability, and are an ideal choice for the new generation of high-energy thermal batteries. However, due to the poor fluoride ion conductivity of the discharge product fluoride of the highly active metal negative electrode (such as AlF 3 :10 -11 S / cm), so that the fluorination reaction of the metal negative electrode during discharge is limited to the surface of the grains, and a fluoride layer is formed at the interface between the negative electrode and the electrolyte, which hinders the fluorination reaction from proceeding deeply in the negative electrode, seriously affecting the discharge capacity and energy density of the fluoride ion thermal battery. Summary of the invention

[0004] In order to solve the technical problem that the fluoride produced by the active metal negative electrode hinders the reaction during high-temperature discharge of a fluoride ion thermal battery, the present invention provides an alloy negative electrode material and a preparation method thereof, and a fluoride ion thermal battery prepared therefrom.

[0005] In order to achieve the above object, the present invention adopts the following technical solution: an alloy negative electrode material, including 0.5% to 30% rare earth metal and 70% to 99.5% high activity metal in terms of mass percentage.

[0006] The rare earth metal is one or more of La, Ce, Nd and Sm.

[0007] The highly active metal is one or more of Mg, Al, Ti, Zn, Sn, Pb, and Bi.

[0008] The purity of the rare earth metal and the high-activity metal is greater than 99%.

[0009] The method for preparing the above alloy negative electrode material comprises the following steps:

[0010] (1) weighing rare earth metals and highly active metals according to a target stoichiometric ratio and mixing them uniformly;

[0011] (2) placing the mixed material in a high-temperature melting furnace, heating and melting it under a special atmosphere and keeping it warm;

[0012] (3) After the heat preservation is completed, the liquid alloy material is cast into a mold, and after cooling and solidification, a master alloy is obtained;

[0013] (4) The master alloy is treated by a plasma rotating electrode method to obtain alloy powder.

[0014] The rare earth metal and high-activity metal are in the form of one or more of powder, strip, foil and block.

[0015] The special atmosphere is one of argon or nitrogen, and the purity is 99.99% or above.

[0016] The heating and melting temperature is 200-1500°C.

[0017] The heat preservation time is 1 to 6 hours.

[0018] A fluoride ion thermal battery, the negative electrode material of which adopts the above alloy negative electrode material or the alloy negative electrode material prepared by the above preparation method.

[0019] The beneficial effects of the present invention are as follows: the alloy material is prepared by high-temperature smelting, the preparation method is convenient, the raw materials are simple and easy to obtain, and the alloy composition is reasonably designed: the rare earth metal electrode has a lower potential and higher reduction activity, and is preferentially fluorinated in the discharge reaction to generate rare earth metal fluorides with higher fluoride ion conductivity. The uniform rare earth metal in situ constructs a fluoride ion fast transmission channel in the alloy negative electrode, improves the ion conductivity of the negative electrode material, increases the reaction depth of the negative electrode active metal fluorination, avoids the passivation layer generated at the negative electrode electrolyte interface by the fluorination of a single active metal negative electrode, and is beneficial to improving the energy density of the fluoride ion thermal battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 This is a physical picture of the lanthanum aluminum alloy powder material prepared in Example 1 of the present invention;

[0021] Figure 2This is a SEM image of the lanthanum aluminum alloy powder material prepared in Example 1 of the present invention;

[0022] Figure 3 The discharge curve of the fluoride ion thermal battery assembled in Application Example 1 of the present invention;

[0023] Figure 4 This is a discharge curve diagram of the fluoride ion thermal battery assembled in Comparative Example 1 of the present invention; DETAILED DESCRIPTION

[0024] The present invention is further described below in conjunction with specific embodiments. The embodiments described below with reference to the accompanying drawings are exemplary and are intended to be used to explain the present invention, but should not be construed as limiting the present invention. In addition, it should be understood that after reading the contents disclosed in the present invention, those skilled in the art may make various changes or modifications to the present invention, and these equivalent forms also fall within the scope of protection defined by the present invention.

[0025] The alloy negative electrode material of the present invention comprises, in terms of mass percentage, 0.5% to 30% of rare earth metal and 70% to 99.5% of high-activity metal.

[0026] The rare earth metal is one or more of La, Ce, Nd and Sm.

[0027] The highly active metal is one or more of Mg, Al, Ti, Zn, Sn, Pb, and Bi.

[0028] The purity of the rare earth metal and the high-activity metal is greater than 99%.

[0029] The method for preparing the above alloy negative electrode material comprises the following steps:

[0030] (1) weighing rare earth metals and highly active metals according to a target stoichiometric ratio and mixing them uniformly;

[0031] (2) placing the mixed material in a high-temperature melting furnace, heating and melting it under a special atmosphere and keeping it warm;

[0032] (3) After the heat preservation is completed, the liquid alloy material is cast into a mold, and after cooling and solidification, a master alloy is obtained;

[0033] (4) The master alloy is treated by a plasma rotating electrode method to obtain alloy powder.

[0034] The rare earth metal and high-activity metal are in the form of one or more of powder, strip, foil and block.

[0035] The special atmosphere is one of argon or nitrogen, and the purity is 99.99% or above.

[0036] The heating and melting temperature is 200-1500°C.

[0037] The heat preservation time is 1 to 6 hours.

[0038] A fluoride ion thermal battery, the negative electrode material of which adopts the above alloy negative electrode material or the alloy negative electrode material prepared by the above preparation method.

[0039] Example 1

[0040] 250 g of rare earth metal La powder with a purity of 99.9% and 750 g of high-activity metal Al powder with a purity of 99.9% were weighed respectively, mixed evenly for 30 minutes, and placed in a crucible; the crucible was placed in a high-temperature melting furnace, heated to 1500° C. in a high-purity argon atmosphere with a purity of 99.99%, melted and kept warm for 6 hours; after the insulation was completed, the liquid alloy material was cast into a mold, and a master alloy was obtained after cooling and solidification; the master alloy was treated with a plasma rotating electrode method to obtain a lanthanum aluminum alloy powder.

[0041] Example 2

[0042] 5 g of a rare earth metal Ce block with a purity of 99% and 995 g of a high-activity metal Mg bar with a purity of 99.5% were weighed respectively, mixed evenly for 20 minutes, and placed in a crucible; the crucible was placed in a high-temperature melting furnace, heated to 850°C for melting and kept warm for 6 hours in a high-purity argon atmosphere with a purity of 99.99%; after the insulation, the liquid alloy material was cast into a mold, and a master alloy was obtained after cooling and solidification; the master alloy was treated with a plasma rotating electrode method to obtain a cerium-magnesium alloy powder.

[0043] Example 3

[0044] 300 g of rare earth metal La powder with a purity of 99.9%, 300 g of high-activity metal Mg strip with a purity of 99.5%, and 400 g of high-activity metal Al foil with a purity of 99.9% were weighed respectively, uniformly mixed for 30 minutes, and placed in a crucible; the crucible was placed in a high-temperature melting furnace, heated to 750° C. for melting and kept warm for 3 hours in a high-purity nitrogen atmosphere with a purity of 99.99%; after the insulation was completed, the liquid alloy material was cast into a mold, and a master alloy was obtained after cooling and solidification; the master alloy was treated by a plasma rotating electrode method to obtain lanthanum-magnesium-aluminum alloy powder.

[0045] Example 4

[0046] 100 g of rare earth metal La powder with a purity of 99.9%, 100 g of rare earth metal Ce block with a purity of 99%, 300 g of high-activity metal Sn powder with a purity of 99.9%, and 500 g of high-activity metal Bi powder with a purity of 99.9% are weighed respectively, uniformly mixed for 30 minutes, and placed in a crucible; the crucible is placed in a high-temperature melting furnace, heated to 200° C. for melting and kept warm for 1 hour in a high-purity nitrogen atmosphere with a purity of 99.99%; after the insulation is completed, the liquid alloy material is cast into a mold, and a master alloy is obtained after cooling and solidification; the master alloy is treated by a plasma rotating electrode method to obtain a lanthanum, cerium, tin, and bismuth alloy powder.

[0047] Application Example 1

[0048] The lanthanum aluminum alloy powder in Example 1 was used as the negative electrode material, LiF-NaF-KF / MgO was used as the electrolyte separator material, and NiF 2 As the positive electrode material, it was pressed into a 18mm electrode sheet under 5 tons of pressure, and a heating unit was added to assemble it into a single cell. Eight single cells were connected in series to assemble a fluoride ion thermal battery, and a discharge experiment was carried out with a constant current of 50mA / cm 2 , 500mA / cm every 15s after activation 2 The pulse current, discharge curve is as follows Figure 3 shown.

[0049] Comparative Example 1

[0050] The single component metal Al powder is used as the negative electrode material, LiF-NaF-KF / MgO is used as the electrolyte separator material, and NiF 2 As the positive electrode material, it was pressed into a 18mm electrode sheet under 5 tons of pressure, and a heating unit was added to assemble it into a single cell. Eight single cells were connected in series to assemble a fluoride ion thermal battery, and a discharge experiment was carried out with a constant current of 50mA / cm 2 , 500mA / cm every 15s after activation 2 The pulse current, discharge curve is as follows Figure 4 shown.

[0051] The discharge curve results of the fluoride ion thermal battery assembled by the application example 1 and the comparative example 1 show that when 15V is selected as the cut-off voltage, the discharge time of the fluoride ion thermal battery with a lanthanum aluminum alloy negative electrode is extended by 80% compared with the discharge time of the fluoride ion battery with a single metal aluminum negative electrode, and the average internal resistance is reduced by 50%, indicating that through the reasonable alloying design of the metal negative electrode of the fluoride ion thermal battery, a fast fluoride ion transmission network is constructed, which effectively reduces the discharge internal resistance, improves the discharge depth, and prolongs the discharge time.

[0052] The experimental results are shown in the table below.

[0053] Particle size D50 Activation time Single peak pressure Discharge time Average internal resistance Comparative Example 1 20μm 0.20s 2.08V 130s 2.45Ω Example 1 20μm 0.20s 2.09V 225s 1.31Ω Example 2 47μm 0.21s 2.11V 189s 1.90Ω Example 3 31μm 0.19s 2.18V 243s 1.28Ω Example 4 55μm 0.19s 2.15V 172s 1.51Ω

[0054] The experimental results show that, thanks to the lower electrode potential of the rare earth metal material and the higher fluoride ion conductivity of its discharge product, the alloy material negative electrode prepared in Examples 1-4 has a fluoride ion thermal battery discharge time extended by more than 30% and an average internal resistance reduced by more than 20% compared with the single active metal material negative electrode composition of Comparative Example 1, proving that a reasonably designed alloyed negative electrode effectively improves the discharge performance of the fluoride ion thermal battery.

[0055] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. An alloy negative electrode material, characterized in that: According to mass percentage, it includes 0.5% to 30% rare earth metal and 70% to 99.5% high activity metal.

2. The alloy negative electrode material according to claim 1, characterized in that: The rare earth metal is one or more of La, Ce, Nd and Sm.

3. The alloy negative electrode material according to claim 1, characterized in that: The highly active metal is one or more of Mg, Al, Ti, Zn, Sn, Pb, and Bi.

4. The alloy negative electrode material according to claim 1, characterized in that: The purity of the rare earth metal and the high-activity metal is greater than 99%.

5. The method for preparing the alloy negative electrode material according to any one of claims 1 to 4, characterized in that: The steps include: (1) weighing rare earth metals and highly active metals according to a target stoichiometric ratio and mixing them uniformly; (2) placing the mixed material in a high-temperature melting furnace, heating and melting it under a special atmosphere and keeping it warm; (3) After the heat preservation is completed, the liquid alloy material is cast into a mold, and after cooling and solidification, a master alloy is obtained; (4) The master alloy is treated by a plasma rotating electrode method to obtain alloy powder.

6. The method for preparing the alloy negative electrode material according to claim 5, characterized in that: The rare earth metal and high-activity metal are in the form of one or more of powder, strip, foil and block.

7. The method for preparing the alloy negative electrode material according to claim 5, characterized in that: The special atmosphere is one of argon or nitrogen, and the purity is 99.99% or above.

8. The method for preparing the alloy negative electrode material according to claim 5, characterized in that: The heating and melting temperature is 200-1500°C.

9. The method for preparing the alloy negative electrode material according to claim 5, characterized in that: The heat preservation time is 1 to 6 hours.

10. A fluoride ion thermal battery, characterized in that: The negative electrode material is the alloy negative electrode material described in any one of claims 1 to 4 or the alloy negative electrode material prepared by the preparation method described in any one of claims 5 to 9.

Citation Information

Cited By

  • Molten salt electrolyte material, preparation method thereof and fluorine ion thermal battery prepared from molten salt electrolyte material

    CN121839737A

  • A molten salt electrolyte material, a preparation method thereof and a fluorine ion thermal battery prepared thereby

    CN121839737B